Development of English Travel Guide for Improving Local Tourism Services in Ollon Valley Tourist Attraction, Tana Toraja - Girik Allo, Markus Deli; Sudarsi, Elim Trika; Taula’bi, Nilma (Institute Of Advanced Knowledge and Science, 2024)
The current tour guides do not meet the needs of local tour guides in the Ollon Valley, so it is necessary to develop travel guides tailored to their needs. Next, the lack of use of technology in the provision of Ollon Valley tour guides, makes it difficult for local tour guides to access up-to-date and accurate information about attractions. And lastly from the aspect of cross-cultural communication, cultural and linguistic differences between local tour guides and foreign tourists can lead to misunderstandings and make the tourist experience less enjoyable, so a better English-speaking travel guide is needed to facilitate better communication between the two parties. In the research on